2010
DOI: 10.1177/156482651003100221
|View full text |Cite
|
Sign up to set email alerts
|

Infant and Young Child Feeding Indicators and Determinants of Poor Feeding Practices in India: Secondary Data Analysis of National Family Health Survey 2005–06

Abstract: Background. In India, poor feeding practices in early childhood contribute to the burden of malnutrition and infant and child mortality.Objective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
138
12
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(179 citation statements)
references
References 18 publications
27
138
12
2
Order By: Relevance
“…In developed countries, rates for six months of exclusive breastfeeding were found to be low: 16.3% in the United States [9], 13.8% in Canada [10] and 13.4% in Hong Kong [11]. Higher prevalence was found in developing county like Indonesia 42%6 and India 46.4% [12]. In previous study, some factors had positive associations with breastfeeding duration.…”
Section: Discussionmentioning
confidence: 96%
“…In developed countries, rates for six months of exclusive breastfeeding were found to be low: 16.3% in the United States [9], 13.8% in Canada [10] and 13.4% in Hong Kong [11]. Higher prevalence was found in developing county like Indonesia 42%6 and India 46.4% [12]. In previous study, some factors had positive associations with breastfeeding duration.…”
Section: Discussionmentioning
confidence: 96%
“…Access to medical appointments during prenatal has been identified in the literature as a protective factor for breastfeeding within one hour of birth 13,36 . Data from Uganda PNDS, conducted in 2006, showed that women who sought prenatal care were more likely to breastfeed within the first hour (6 to 7%) when compared to those who did not seek prenatal care 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The literature has indicated that the practices of health professionals 8,[13][14][15][16][17][18] , as well as the organization and management of health services, are essential to the initiation of breastfeeding immediately after childbirth 12 . Mothers who got the prenatal care 13 , who were counseled during prenatal about breastfeeding 18 and who received postpartum assistance from health professionals for breastfeeding were more likely to breastfeed their children in the first hour 16,17 . With regard to health services, allowing companion in childbirth, having deliveries paid by the Unified Health System (SUS) and in hospitals that received the title of Child Friendly Hospital Initiative (IHAC) 12 were appointed as stimulating factor for the breastfeeding within one hour of birth.…”
Section: Palavrasmentioning
confidence: 99%
“…Some common factors such as changing lifestyles, aggressive promotion of formula milk, a general unawareness of the importance of breast-feeding and perceived insufficiency of milk could play important roles in contributing towards suboptimal feeding practices. In women delivered through Caesarean section there is a perceived insufficiency of milk contributing towards high bottle-feeding rate, which is a common finding in India, Nepal, Sri Lanka and China where it was the main reason for delayed contact (21,(34)(35)(36) . This perceived insufficiency was also found to be the most common cause for discontinuing breast-feeding of children in Australia (37) .…”
Section: Discussionmentioning
confidence: 99%